Upper GI endoscopy in subjects with positive fecal occult blood test undergoing colonoscopy: systematic review and meta-analysis - Shah, Ayesha; Eqbal, Ali; Moy, Naomi; Koloski, Natasha; Messmann, Helmut; Kendall, Bradley J.; Sharma, Prateek; Dulleck, Uwe; Jones, Michael P.; Holtmann, Gerald J. (Gastrointestinal endoscopy, 2023)
The role of gastroscopy to investigate the upper GI (UGI) tract in subjects with a positive fecal occult blood test (FOBT+) result is controversial. We conducted a systematic review and meta-analysis, which aimed to determine the prevalence of UGI lesions in FOBT+ subjects. Databases were searched until March 31, 2022 for studies reporting UGI lesions in FOBT+ subjects undergoing colonoscopy and gastroscopy. Pooled prevalence rates of UGI cancers and clinically significant lesions (CSLs; lesions potentially explaining occult blood loss), odds ratio (OR), and 95% confidence intervals (CIs) were calculated. We included 21 studies with 6993 FOBT+ subjects. Pooled prevalence of UGI cancers was .8% (95% CI, .4-1.6) and UGI CSLs was 30.4% (95% CI, 20.7-42.2), and that of colonic cancers and CSLs was 3.3% (95% CI, 1.8-6.0) and 31.9% (95% CI, 23.9-41.1), respectively. There was no significant difference in the prevalence of UGI CSL and UGI cancers in FOBT+ subjects with/without colonic pathology (ORs of 1.2 [95% CI, .9-1.6; P = .137] and 1.6 [95% CI, .5-5.5; P = .460]). Anemia in FOBT+ subjects was associated with UGI cancers (OR, 6.3; 95% CI, 1.3-31.5; P = .025) and UGI CSLs (OR, 4.3; 95% CI, 2.2-8.4; P = .0001). GI symptoms were not associated with UGI CSLs (OR, 1.3; 95% CI, .6-2.8; P = .511). There is an appreciable prevalence of UGI cancers and other CSLs in FOBT+ subjects. Anemia but not symptoms or colonic pathology are linked to UGI lesions. Although the data suggest that same-day gastroscopy in FOBT+ subjects undergoing colonoscopy yields approximately 25% more malignancies as colonoscopy alone, prospective data are required to determine the cost-efficacy of dual endoscopy as a standard of care for all FOBT+ subjects.